Tissue Factor/Factor VIIa Complex: Role of the Membrane Surface - Morrissey, James H. (2012)
Blood clotting is triggered when the plasma serine protease factor VIIa binds to the cell-surface protein, tissue factor (TF); the resulting TF:FVIIa complex activates factors IX (FIX) and X (FX) by limited proteolysis. FVIIa, FIX and FX all bind reversibly to membranes via their gamma-carboxyglutamate-rich (GLA) domains, while TF is an integral membrane protein. Removing these proteases from the membrane surface is known to render them thousands of times less active, although the mechanisms by which blood clotting proteins bind to membranes—and the contributions of membranes to catalysis—remain very incompletely understood. Our recent and ongoing studies use a combination of nanoscale membrane bilayers (Nanodiscs), solid-state NMR and all-atom molecular dynamics (MD) simulations, enabling detailed insights into how GLA domains bind to phospholipid bilayers and how specific phospholipids enhance the catalytic activity of the TF:FVIIa complex.